Implementasi Pendekatan Berbasis Proyek dalam Pembelajaran Fisika: Kajian Sistematis - Saddia, Andi; Amir, Faizal (Journal of Health, Education, Economics, Science, and Technology, 2025)
Physics education is often considered a challenging subject for students, primarily due to its abstract nature and the need for a strong understanding of concepts and mathematical application. Traditional teacher-centered teaching methods often reduce student engagement, leading to low motivation and suboptimal learning outcomes. The project-based learning (PBL) approach offers a promising solution to enhance the effectiveness of physics education by providing authentic learning experiences relevant to real-world situations. In this model, students actively participate in designing, implementing, and evaluating projects that produce real solutions to real-world problems. This approach not only enhances students' understanding of physics concepts but also develops essential 21st-century skills such as critical thinking, problem-solving, collaboration, and communication. This article examines the implementation of the project-based learning approach in physics education with the goal of improving student motivation and engagement. The study also discusses the challenges and strategies for implementing PBL and its relevance in the context of physics education. The findings of this review indicate that PBL implementation can improve physics concept understanding, develop 21st-century skills, and enhance student motivation.